Evolution and Unprecedented Variants of the Mitochondrial Genetic Code in a Lineage of Green Algae - Žihala, David; Eliáš, Marek (Genome biology and evolution, 2019)
Mitochondria of diverse eukaryotes have evolved various departures from the standard genetic code, but the breadth of possible modifications and their phylogenetic distribution are known only incompletely. Furthermore, it is possible that some codon reassignments in previously sequenced mitogenomes have been missed, resulting in inaccurate protein sequences in databases. Here we show, considering the distribution of codons at conserved amino acid positions in mitogenome-encoded proteins, that mitochondria of the green algal order Sphaeropleales exhibit a diversity of codon reassignments, including previously missed ones and some that are unprecedented in any translation system examined so far, necessitating redefinition of existing translation tables and creating at least seven new ones. We resolve a previous controversy concerning the meaning the UAG codon in Hydrodictyaceae, which beyond any doubt encodes alanine. We further demonstrate that AGG, sometimes together with AGA, encodes alanine instead of arginine in diverse sphaeroplealeans. Further newly detected changes include Arg-to-Met reassignment of the AGG codon and Arg-to-Leu reassignment of the CGG codon in particular species. Analysis of tRNAs specified by sphaeroplealean mitogenomes provides direct support for and molecular underpinning of the proposed reassignments. Furthermore, we point to unique mutations in the mitochondrial release factor mtRF1a that correlate with changes in the use of termination codons in Sphaeropleales, including the two independent stop-to-sense UAG reassignments, the reintroduction of UGA in some Scenedesmaceae, and the sense-to-stop reassignment of UCA widespread in the group. Codon disappearance seems to be the main drive of the dynamic evolution of the mitochondrial genetic code in Sphaeropleales.
Keywords: molekulární evoluce; RNA transferová; green algae; mitochondrie; mitogenomes; Chlorophyta; terminační kodon; peptidy - faktory ukončení; Codon; RNA, Transfer; genom mitochondriální; Sphaeropleales; Mitochondrial Proteins; Codon, Terminator; genetic code; codon reassignments; kodon; Mitochondria; Peptide Termination Factors; release factor; Genome, Mitochondrial; mitochondriální proteiny; Evolution, Molecular